2019
DOI: 10.3390/jmse7080245
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Industrial Waste in Cement in a Marine Environment with a Tropical Climate

Abstract: This novel study on cement paste material was conducted with the aim of keeping up with the rapid development of urban construction and contributing to the continuous improvement of building materials to overcome environmental issues. In this study, several kinds of industrial waste were used to enhance the properties of cement paste for application in a marine environment with a tropical climate, such as in Vietnam. This study focuses on evaluating the properties of cement paste containing cement replacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…This result is similar to some studies that showed satisfactory performance in terms of resistance to cyclic freezing and thawing, and deicer salt scaling when PCC ash was replaced by 30% or more [54,55]. In addition, according to the study of Chu et al (2019) [26], the samples with PCC ash had a lower rate of chloride ion and sulfate ion permeability than the control group. The reason is that the presence of PCC ash increases the amount of C3A due to the higher amount of alumina present in the mixture.…”
Section: Durability Properties Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…This result is similar to some studies that showed satisfactory performance in terms of resistance to cyclic freezing and thawing, and deicer salt scaling when PCC ash was replaced by 30% or more [54,55]. In addition, according to the study of Chu et al (2019) [26], the samples with PCC ash had a lower rate of chloride ion and sulfate ion permeability than the control group. The reason is that the presence of PCC ash increases the amount of C3A due to the higher amount of alumina present in the mixture.…”
Section: Durability Properties Analysissupporting
confidence: 88%
“…In addition, there are also research results focusing on the durability of PCC ash concrete as follows. Chuet al (2019) [26] conducted experiments with PCC ash 0~30%, silica fume 0~10%, plasticizer 0.3% and 0.4%, to examine cement pastes for application in tropical climate marine environments such as Vietnam. As a result of the test, the optimum formulation was analyzed to be 20% PCC ash, 10% silica fume, and 0.4% plasticizer.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the defects of concrete materials, exploring and researching new materials and technologies that improve the corrosion resistance of concrete has become a research hotspot. Adding an appropriate amount of admixtures to ordinary concrete components for modification is a more economical way to improve the durability of concrete structures [12]. Fracture mechanics, also called "crack body mechanics", is a discipline that studies the strength of components working with defects or cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Com a adição de cinzas nas pastas cimentícias, observa-se um aumento da perda de água, pois as cinzas da alga de sargaço podem reter partículas de água em seus poros capilares. Além disso, pode ocorrer a desidratação de gel C-S-H e a decomposição de C-S-H sobrepostos com hidratos de sulfoaluminato de cálcio (hidratos de etringita e monossulfato), desidroxilação de CH, bem como produtos de hidratação, os hidratos de aluminossilicato de cálcio (CHU et al, 2019). Dessa forma, observa-se maior decomposição de produtos de hidratação da pastas cimentícias com 10% de cinzas de sargaço.…”
Section: Análise Termogravimétrica Das Pastas Cimentíciasunclassified
“…As amostras das pastas apresentaram comportamentos semelhantes nas análises de difração de raios X, na Figura 24. Observa-se, na Figura 24, na faixa demarcada (30°-35°), as pastas cimentícias com a adição de cinzas de sargaço, o pico de portlandita Ca(OH)2 diminui em intensidade à medida que o nível de acréscimo das cinzas e o aumento da hidratação devido a cinza de sargaço absorver umidade (CHU et al, 2019). A formação de portlandita, produto importante na hidratação do cimento, contribui na resistência das pastas.…”
Section: Difração De Raio X Das Pastas Cimentíciasunclassified